2016
DOI: 10.12973/jesr.2016.61.12
|View full text |Cite
|
Sign up to set email alerts
|

Yabancı dilin İngilizce olarak öğretildiği sınıflarda yüksek ya da düşük bağlamlı kültür?

Abstract: Intercultural communicative competence (ICC) and high-low context culture situations are important for both EFL/ESL teachers and their students. In the EFL context, tertiary level students in Turkey are taught by both native and non-native English speakers, which might be challenging for foreign language students as it causes potential communication breakdowns in the classroom. By regarding cultural values, there is a need to examine how EFL tertiary level students successfully negotiate these cultural differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The findings of the present study, however, revealed that Turkish students experienced difficulty "reading the air" and understanding the topics and conversations in social contexts; therefore, social skills of thoughtful expression were adopted. As both Turkish culture (Karakuzu & Irgin, 2016) and Japanese culture are high-context cultures (Hall & Hall, 1990), social skills of high-context communication such as "reading the air" are essential to able to follow and understand conversations, and to fit the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study, however, revealed that Turkish students experienced difficulty "reading the air" and understanding the topics and conversations in social contexts; therefore, social skills of thoughtful expression were adopted. As both Turkish culture (Karakuzu & Irgin, 2016) and Japanese culture are high-context cultures (Hall & Hall, 1990), social skills of high-context communication such as "reading the air" are essential to able to follow and understand conversations, and to fit the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study, however, revealed that Turkish students experienced difficulty "reading the air" and understanding the topics and conversations in social contexts; therefore, social skills of thoughtful expression were adopted. As both Turkish culture (Karakuzu & Irgin, 2016) and Japanese culture are high-context cultures (Hall & Hall, 1990), social skills of high-context communication such as "reading the air" are essential to able to follow and understand conversations, and to fit the environment.…”
mentioning
confidence: 99%